2012
DOI: 10.2147/ijn.s35751
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based model characterizing bidirectional interaction between PEGylated liposomal CKD-602 (S-CKD602) and monocytes in cancer patients

Abstract: S-CKD602 is a PEGylated liposomal formulation of CKD-602, a potent topoisomerase I inhibitor. The objective of this study was to characterize the bidirectional pharmacokinetic-pharmacodynamic (PK-PD) interaction between S-CKD602 and monocytes. Plasma concentrations of encapsulated CKD-602 and monocytes counts from 45 patients with solid tumors were collected following intravenous administration of S-CKD602 in the phase I study. The PK-PD models were developed and fit simultaneously to the PK-PD data, using NON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Thus, dose reductions may be needed in subsequent cycles to minimize the risk of toxicity. These results and prior results reporting a relationship between the reduction in monocyte counts in blood and the clearance of PEGylated liposomal agents in patients where greater monocyte reductions were associated with greater clearance of the liposomal agents suggest that there is a bidirectional interaction between NPs and the MPS, where the MPS cells take up NPs and the NPs have pharmacologic and/or toxicologic effects on the MPS cells (72,73). Interestingly, repeat dose studies of PEGylated liposomal doxorubicin in mice and rats did not report accumulation of drug in plasma suggesting that these preclinical models may not accurately reflect the disposition of PEGylated liposomal agents after repeated dosing (74,75).…”
Section: Introduction: Safety and Toxicological Effects: A Jacobssupporting
confidence: 74%
“…Thus, dose reductions may be needed in subsequent cycles to minimize the risk of toxicity. These results and prior results reporting a relationship between the reduction in monocyte counts in blood and the clearance of PEGylated liposomal agents in patients where greater monocyte reductions were associated with greater clearance of the liposomal agents suggest that there is a bidirectional interaction between NPs and the MPS, where the MPS cells take up NPs and the NPs have pharmacologic and/or toxicologic effects on the MPS cells (72,73). Interestingly, repeat dose studies of PEGylated liposomal doxorubicin in mice and rats did not report accumulation of drug in plasma suggesting that these preclinical models may not accurately reflect the disposition of PEGylated liposomal agents after repeated dosing (74,75).…”
Section: Introduction: Safety and Toxicological Effects: A Jacobssupporting
confidence: 74%
“…[18][19][20] We have also reported that monocytes are more sensitive to S-CKD602 compared with neutrophils, and the increased sensitivity is related to the liposomal formulation and not CKD-602. 21,22 These results suggest that monocytes engulf S-CKD602, which causes the release of CKD-602 from the liposome and toxicity to the monocytes, and that the effects are more prominent in patients aged ,60 years. 20,22,23 We were also the first group to report that body composition alters the pharmacokinetics of PEGylated liposomal agents in mice and in patients.…”
mentioning
confidence: 88%
“…Pharmacokinetic model parameters for sum total CPT-11 after administration of IHL-305 included the volume of the central compartment (V c ) and intercompartment rate constants, (k 12 , k 21 ). 29 The elimination rate constant from the central compartment (k 10 ) was used to represent linear clearance.…”
Section: Compartmental Pharmacokinetic Analysismentioning
confidence: 99%
“…Taxanes are known to interact with tumor-associated macrophage and circulating monocytes and cause leukopenia [35]. It is also known that circulating monocytes regenerate every 2-3wk, are recruited into the tumor compartment from the circulation, where they differentiate into macrophage [36].…”
Section: Discussionmentioning
confidence: 99%